2017
DOI: 10.1038/ncomms15789
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variants in ARHGAP15, COLQ and FAM155A associate with diverticular disease and diverticulitis

Abstract: Diverticular disease is characterized by pouches (that is, diverticulae) due to weakness in the bowel wall, which can become infected and inflamed causing diverticulitis, with potentially severe complications. Here, we test 32.4 million sequence variants identified through whole-genome sequencing (WGS) of 15,220 Icelanders for association with diverticular disease (5,426 cases) and its more severe form diverticulitis (2,764 cases). Subsequently, 16 sequence variants are followed up in a diverticular disease sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 55 publications
(75 reference statements)
8
73
0
4
Order By: Relevance
“…Thirty-six out of 48 identified risk loci have been previously reported15 with genome-wide significant association (tables 2 and 3 and online supplementary table 4). All previously replicated risk loci for diverticular disease ( ARHGAP15 , FAM155A , COLQ) and ( GPR158, ABO, ANO1/FADD, ELN, BMPR1B, SLC35F3, SEM1/SHFM1 ) were identified both in the current GWAS and replication analyses with similar ORs to those reported by Sigurdsson et al 14 and Maguire et al 15 (table 3). The most significant novel risk variant rs9960286 is located near CTAGE1 (cutaneous T-cell lymphoma-associated antigen 1) with a p value of 2.3×10 −10 and 0.002 (OR allelic =1.14 (95% CI 1.05 to 1.24)) in the replication analysis.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Thirty-six out of 48 identified risk loci have been previously reported15 with genome-wide significant association (tables 2 and 3 and online supplementary table 4). All previously replicated risk loci for diverticular disease ( ARHGAP15 , FAM155A , COLQ) and ( GPR158, ABO, ANO1/FADD, ELN, BMPR1B, SLC35F3, SEM1/SHFM1 ) were identified both in the current GWAS and replication analyses with similar ORs to those reported by Sigurdsson et al 14 and Maguire et al 15 (table 3). The most significant novel risk variant rs9960286 is located near CTAGE1 (cutaneous T-cell lymphoma-associated antigen 1) with a p value of 2.3×10 −10 and 0.002 (OR allelic =1.14 (95% CI 1.05 to 1.24)) in the replication analysis.…”
Section: Resultssupporting
confidence: 87%
“…Among these loci, 12 are novel risk loci for diverticular disease and 5 of the novel loci were also replicated in a European clinical cohort with detailed phenotyping and colonoscopy data for all controls. The three previously known risk loci14 ARHGAP15 , COLQ and FAM155A are among the validated loci and support the robustness of the phenotype and analysis on both the previous study and our analysis. A recent study by Maguire et al 15, who analysed a smaller UK Biobank dataset (n=409 728 individuals) compared with the current study (n=451 099) identified 40 loci with genome-wide significance using GWAS results publicly available from the Roslin Gene Atlas.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Twin studies reveal that genetic heritability of diverticular disease is estimated to be up to 53% (95% Confidence Interval (CI), 45-61%) 6 . To date, three GWAS have identified 52 genetic susceptibility loci associated with diverticular disease [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%